2020
DOI: 10.3390/met10020183
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Chalcopyrite with an Imidazolium-Based Ionic Liquid and Bromide

Abstract: The unique properties of ionic liquids (ILs) drive the growing number of novel applications in different industries. The main features of ILs are high thermal stability, recyclability, low flash point, and low vapor pressure. This study investigated pure chalcopyrite dissolution in the presence of the ionic liquid 1-butyl-3-methylimidazolium hydrogen sulfate, [BMIm]HSO4, and a bromide-like complexing agent. The proposed system was compared with acid leaching in sulfate media with the addition of chloride and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Rodríguez et al [15] offered their research paper entitled "Leaching Chalcopyrite with an Imidazolium-Based Ionic Liquid and Bromide". The unique properties of ionic liquids (ILs) drive the growing number of novel applications in different industries.…”
Section: Contributionsmentioning
confidence: 99%
“…Rodríguez et al [15] offered their research paper entitled "Leaching Chalcopyrite with an Imidazolium-Based Ionic Liquid and Bromide". The unique properties of ionic liquids (ILs) drive the growing number of novel applications in different industries.…”
Section: Contributionsmentioning
confidence: 99%
“…There have been a number of recent studies applying ionic liquids to chalcopyrite, summarized by Rodriguez et al [32]. Results from the first study by Whitehead et al [33] showed copper leaching rates increased from 55% to 87% when increasing the concentration of ionic liquid (1-butyl-3-methyl-imidazolium hydrogen sulfate) from 10 to 100% in aqueous solution, at 70°C.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Among the copper minerals on the planet, the vast majority correspond to sulfide ores [3]. Within these copper minerals, chalcopyrite stands out as the most abundant, representing 70% of all minerals that contain copper in the Earth's crust [4][5][6][7]. Copper is recovered from these minerals mainly through flotation, followed by pyrometallurgical processing, representing 80-85% of world's copper production [8,9].…”
Section: Introductionmentioning
confidence: 99%